Knowledge transfer in global supply chains: Multinationals in Sub-Saharan Africa - Lucia Pérez-Villar; Adnan Seric (Kiel Institute for the World Economy (IfW), 2015)
We analyze in this paper determinants of voluntary knowledge transfer from foreign investors to their local suppliers in 19 Sub-Saharan African countries using data from the 2010 Africa Investor Survey by UNIDO. We argue that not all backward linkages entail the same potential for spillovers since not all local sourcing activities by multinationals involve a transfer of knowledge to suppliers. Our findings support the idea that foreign investor's heterogeneity and country environment are key factors shaping the spillover potential of backward linkages. Local management autonomy and the long-term nature of local procurement contracts are positively associated with the transfer of knowledge. Also sourcing strategies that seek to meet local market requirements, to optimize value chain efficiency and that respond to social responsibility commitments are more likely to involved a transfer of knowledge to suppliers. Additionally, host country institutional quality and institutional distance relative to the origin country of the MNE are relevant determinants of the degree of knowledge transfer. Investment policies that merely focus on promoting larger shares of locally sourced inputs might fail to get the most of FDI positive externalities. Instead, quality linkages that involve a transfer of knowledge should be promoted over quantity linkages.
Keywords: F23; O33; 330; knowledge transfer; global value chains; institutional distance; supplier upgrading; sub-Saharan Africa